Increasing Employee Productivity Through Visionary Leadership, Work Environment, And Work Discipline: The Mediation Role Of Organizational Innovation - Tjasmana, Felicia; Sigit Dani Nugroho; Agus Riyanto (Jurnal Ekonomi, 2024)
The background of this research departs from the need to improve understanding of the role of innovation in mediating visionary leadership and the work environment in increasing productivity, considering the importance of innovation as a driver of competitive advantage in a dynamic global era. The study explores the impact of visionary leadership, work environment, and work discipline on employee productivity, influenced by organizational innovation. This study focuses on the staff of Lulu Group Retail Indonesia, using accidental sampling to obtain 250 samples. This descriptive and quantitative research uses Smart PLS3 to process and test Structural Equation Modeling (SEM) hypotheses. The study reveals that visionary leadership and a positive work environment significantly impact employee productivity, while organizational innovation has a direct and substantial impact. However, work discipline variables do not directly and significantly affect employee productivity. However, work discipline mediated by organizational innovation indirectly has a significant influence. In contrast, visionary leadership and work environments mediated by organizational innovation have no indirect or insignificant effect on employee productivity. From the results of this study, in the context of the object of research, visionary leadership is not yet strong enough to encourage innovation to create employee productivity.